Business Intelligence for New-Generation Managers - Mayer, Jörg H (Springer, 2015)
Executives in Europe have significantly expanded their role in operations – in parallel to their strategic leadership. At the same time, they need to make decisions faster than in the past. In these demanding times, a redesigned Business Intelligence (BI) should support managers in their new roles. This book summarizes current avenues of development helping managers to perform their jobs more productively by using 'BI for managers' as their central, hands-on, day-to-day source of information – even when they are mobile.